PENGARUH FAKTOR INTERNAL DAN EKSTERNAL TERHADAP KEIKUTSERTAAN PASANGAN USIA SUBUR DALAM PROGRAM KELUARGA BERENCANA DI WILAYAH KERJA PUSKESMAS TANJUNG BOTUNG KABUPATEN PADANG LAWAS TAHUN 2015 - RATNA WULANDARI (LP2MTBM MAKARIOZ, 2020)
Keep participating as productive aged in a Family Planning (KB) coverage Puskesmas Tanjung Botung is noted lower yet seen about 28.13%. This indicated that a gaining target in KB program not achieved as goal that has been made by Dinas Pemberdayaan Perempuan and Keluarga Berencana (PP dan KB) unit service for rate of 85%. The objective of this study is to analyze the influence of internal factor (family supports, religion encouraged and personnel behavior) against their participation in productive aged on the program noted for 2015.This study is an analytical survey research with cross sectional design method involved the population as all subject productive aged listed and living around the coverage Puskesmas Tanjung Botung serviced area for 2015, totally 263 respondents, to determine them in random sampling technique and taken 73 as sample. In analyzing the data is with multiple logistic regression test.Bases to data of statistic analysis as done, noted that the internal factor influence (knowledge p = 0.004 and attitude p = 0.031) and external factor (family support with p = 0.002), religion support with p = 0.004 and attitude p = 0.031) while attitude factor of personnel have no influence (p=0.165), further the analysis of multi-variant with multiple logistic regression test known that the most dominant factor influencing those participants is such as factor of knowledge with the output gained with p-value = 0.004 and Exp (B) = 36.619.It is suggestible that personnel should be more improving their quality of services to public and take actively participate in serving KB publicly, also encourage to establish and activate Posyandu unit post for each village administration and make socialization about the existence of KB program.